Ética e comportamento moral dos servidores públicos – um estudo de caso no IFCE Campus do Crato - Trigueiro, Emília Suitberta de Oliveira (2012)
Ethics is a very important theme since it guides social life. It is influenced by time, history and culture in which it is inserted. In organizartions, ethics straight influences profits and results. For this, there is a great number of studies and discussions on this subject as a result of employees’ personal ethics. In relation to public organizational ethics there are several critics. Among them, the fact public servants do not have ethical behavior, public service do not work appropriately, the value of personal interests contrasting corporate ones in these places. Nevertheless, there are not many studies analysing this point. Within this research, it aims at identifying what Ceará Federal Unstitute-at campus Crato-faculty and technical administrative servants understanding are about ethical concepts and how these moral behaviors are made throughout their labor practice. For this, it was developed a descriptive research carried by eletronic device, with 44 servants in this institution. It was based on Badin’s theories to analyse the ethics concept of these servants extracted by the Word Association Test and the Instrument to analyse the moral behavior under organizations, developed by Llcht, based on Patrick and Wagley’s theory. The main founded results speak about divergence between servants’ theory and labor practice, since they individually demonstrate notions on what ethics would be, with a solid concept according to Public Servant Ethical Code. Otherwise, the whole organization was classified in the level of organizational development as pre-moral or pre-convencional. This leads us to conclude that not always the person express in his/her behavior the ethical basis he/she preaches since collectivities exert a great influence on the behavior of the components.